MOST stationery inventory management system - Hassan, Ummi Kalsom; Kasim, Shahreen; Hassan, Rohayanti; Mahdin, Hairulnizam; Ramli, Azizul Azhar; Md Fudzee, Mohd Farhan; Salamat, Mohamad Aizi (Zibeline Internasional Publishers, 2018)
Most Stationery Inventory Management is a system that is built to facilitate the outgoing management of the stationery stock. The main objective of developing this system is to help inventory operator of Most Stationery shop to manage their inventory in a systematic and efficient way. Through the interview, the problem found is stationery stock inventory management still using the manual method to record stationery stock from the stored record file. All the stationeries are divided into file categories in which the suppliers and tools are based on invoice or bills provided. Besides, daily sales report cannot be generated due to the manual sales record produced. Therefore, profit report cannot be generated at the end of month. In a whole, the developed inventory management system can speed up the process of recoding the inventory information to generate the required report by the operators.